Electronic starter for DC motors - Bhatnagar, Arpita; Agarwal, Priya; Gandhi, Kapil; Parchha, Lalit; Kumar, Sandeep (IJRDO - Journal of Electrical And Electronics Engineering, 2017)
The objective of our project is to use the automatic starter for the starting of the dc motor. Commonly 3-point or 4-point starters are used for starting of dc motors. In our project, the device based on the triggering of the thyristors is used. This reduces the mechanical stress on the motor and thus increases the life of the motor. At the time of starting, the value of armature current is very high and in order to limit the high starting current a resistor is connected in between the supply and dc motor. Resistor is divided in several parts and across each part thyristors are connected parallel to it. When dc supply is connected to motor, due to presence of resistor in between supply and motor, motor will get less voltage and current than the rated voltage and rated current. So, at start motor will start slowly. In order to cut out the resistors thyristors have to be fired after specific intervals.